Effects of Experiential Learning Programmes on Adolescent Prosocial Behaviour, Empathy, and Subjective Well-being: A Systematic Review and Meta-Analysis - Chan, Hannah Hoi-Kiu; Kwong, Ho Yee Chloe; Shu, Geisty Lin Feng; Ting, Chung Yan; Lai, Frank Ho-Yin (Frontiers in Psychology, 2021)
Introduction: Effective adolescent learning programmes can positively influence adolescent development and curb risky behaviour. By immersing learners in an experience, experiential learning motivates learners to reflect on the experience to transform and create new skills, attitudes and ways of thinking. Experiential learning based on Kolb’s Experiential Learning Theory and Model (1984) is an engaging and effective method of learning adopted in many learning programmes. Kolb’s Experiential Learning Theory and Model (1984) describes four key elements in the cycle of learning: concrete experience, reflective observation, abstract conceptualization and active experimentation. However, evidence of its effectiveness in learning programs facilitating positive youth development is still lacking. Methods: This study was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Randomized controlled trials of learning programmes for typically developing adolescents aged 8-25 in the past 15 years were identified, and assessed for quality with the Physiotherapy Evidence Database (PEDRO) scale. 1096 records were screened with the inclusion and exclusion criteria, and 20 studies were adopted for this meta-analysis. Forest plots were made regarding the standardized mean difference of each outcome on the selected studies, and the standardized mean difference and 95% confidence interval (CI) of the effect of experiential learning program on empathy, prosocial behaviour, and subjective wellbeing were examined. Sub-group analysis based on age was conducted to examine the effects of experiential learning on adolescents in different stages of life. Results: Experiential learning programmes were more effective than non-experiential learning programmes in improving empathy (d = 0.65 [0.07, 1.23]), prosocial behaviour (d =0.14 [-0.36, 0.63) and subjective wellbeing (d = 0.46 [0.33, 0.59]). Non-experiential learning programmes had the most profound effect on subjective wellbeing (d = 0.11 [-0.04, 0.26]) out of the three outcomes. Studies conducted on older adolescents had the most significant improvements in the three outcomes. Conclusions: Results suggest the broader application of experiential learning in adolescent learning programmes for older adolescents in the future to promote positive youth development.